2016
DOI: 10.1007/s00134-016-4479-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of time to death in hospital in critically ill patients around the world

Abstract: Duration of hospital stay prior to death in critically ill patients is longer in older patients, surgical patients, and patients with infection. GNI is a major determinant of time to death in hospital in these patients. These observations may have important organizational and ethical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Critical illness is a disease condition comprising a remarkable heterogeneity of underlying insults, such as shock, infections, metabolic derangements, burns, trauma, or severe blood loss. Despite these broad range of different initial causes, the body's response to such threats is relatively uniform, and severity of critical illness is determined by the degree of systemic inflammation and subsequent hemodynamic changes, the extent of biological stress, the resultant organ failure(s) and, ultimately, death . Circulating mediators of such core pathways could serve as prognostic biomarkers in critical care medicine …”
Section: Introductionmentioning
confidence: 99%
“…Critical illness is a disease condition comprising a remarkable heterogeneity of underlying insults, such as shock, infections, metabolic derangements, burns, trauma, or severe blood loss. Despite these broad range of different initial causes, the body's response to such threats is relatively uniform, and severity of critical illness is determined by the degree of systemic inflammation and subsequent hemodynamic changes, the extent of biological stress, the resultant organ failure(s) and, ultimately, death . Circulating mediators of such core pathways could serve as prognostic biomarkers in critical care medicine …”
Section: Introductionmentioning
confidence: 99%
“…Further efforts should be made from scientific societies to adequately provide resources for this population. A worldwide study demonstrated that gross national income (GNI) was a major determinant of time to death in hospital in ICU patients [7]. Not only GNI but also age (older patients), type of population (surgical), and infection increased the duration of hospital stay prior to death in critically ill patients.…”
Section: "Area Of Need" Population Studies In Sepsismentioning
confidence: 99%
“…However, the idea that pneumonia should be treatable drives a reluctance to shift to more comfort care measures in patients undergoing prolonged mechanical ventilation. 5 To expect new antibiotics, optimized pharmacokinetics/ pharmacodynamic protocols, and antibiotic stewardship to lead to improved outcomes for patients with HAP/ VAP meets Einstein's definition of insanity, paraphrased as "doing the same thing over and over again and expecting different results." Although each of these measures may have an important role in slowing the development of resistance, they are unlikely to decrease morbidity or mortality.…”
Section: Bell Bg Schellevis F Stobberingh E Goossens H Pringle Mmentioning
confidence: 99%